A fresh look at AGN spectral energy distribution fitting with the XMM-SERVS AGN sample. Issue 4 (15th July 2022) - Marshall, Adam; Auger-Williams, Matthew W; Banerji, Manda; Maiolino, Roberto; Bowler, Rebecca
ABSTRACT: We perform spectral energy distribution (SED) fitting to 711 luminous X-ray AGN at 0.7 < z < 4.5 using 10-bands of optical and infra-red photometric data for objects within XMM-SERVS. This fitting provided 510 reliable (reduced χ 2 < 3) inferences on AGN and host galaxy properties. The AGN optical (3000 Å) luminosity inferred from SED-fitting is found to correlate with the measured X-ray (2–10 keV) luminosity, in good agreement with previous work. Using X-ray hardness as a proxy for AGN obscuration, we also study the differences in the host galaxy properties of obscured and unobscured AGNs. Both populations have consistent stellar masses (log10 ( M * / M ⊙ ) = 10.88 ± 0.09 M_ and log10 ( M * / M ⊙ ) = 10.8 ± 0.1 M_ for unobscured and obscured AGNs, respectively). We also find evidence for varying AGN emission line properties from a standard AGN template in 18.8 per cent of the sample with a reduced χ 2 < 3 where the inclusion of an additional emission line strength free parameter was found to improve the quality of the fit. Comparison of these fits to SDSS spectra showed that emission line properties inferred from broad-band photometry were consistent with the results from spectroscopy for 91 per cent of objects. We find that the presence of weaker, more blueshifted emission lines as inferred from the SED fits are associated with more negative values of αox . While the correlation between the hardness of the ionizing SED and the emission line properties has been known for some time, we are able to derive this correlation purely from broad-band photometry.